THE THE IMPACT OF MACROECONOMIC FACTORS ON SUSTAINABILITY (SDGS) IN ASEAN: A PANEL DATA ANALYSIS - Tongam Sihol Nababan; Ferry Panjaitan; Budiman N.P.D. Sinaga; Ayu Wandira Nainggolan (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This study aims to analyze the influence of macroeconomic factors on the achievement of sustainability indices (Sustainable Development Goals/SDGs) in ASEAN countries. The data used is secondary data in the form of panel data from 10 ASEAN countries for the period 2000–2023. The independent variables include public debt (PD), exchange rate (ER), foreign direct investment (FDI), trade openness (TO), global inflation rate (GIR), and economic crisis (EC). The study uses panel data regression analysis with a fixed effects approach. The model selection is based on the Chow, LM, and Hausman tests. Then, the cluster-robust standard error method was used to overcome the problems of heteroscedasticity and autocorrelation. The results showed that public debt, global inflation rate, and economic crisis had a negative and significant effect on sustainability (SDGs index). Meanwhile, exchange rate, trade openness, and FDI had a positive and significant effect on sustainability (SDGs index).